Association Between Pesticide Exposure and Type 2 Diabetes Mellitus Among Female Farmers: A Cross-Sectional Study - Masyithah, Wulan; Onny Setiani; Yusniar Hanani Darundiati; Mursid Raharjo; Nurjazuli (Universitas Airlangga, 2025)
Introduction: The widespread use of pesticides in agriculture has been linked to an increased risk of diabetes mellitus. Long-term exposure to pesticides can disrupt glucose metabolism, trigger insulin resistance, and raise susceptibility to diabetes mellitus. This study investigates the association between pesticide exposure and the incidence of type 2 diabetes mellitus. Methods: This analytical observational study with a cross-sectional design involved 162 female farmers selected by purposive sampling from a population of 2,187, using the Lemeshow formula. Independent variables included work duration, types and frequency of pesticide use, spraying duration and direction, PPE usage, and cholinesterase levels. The dependent variable was type 2 diabetes mellitus. Data were collected through questionnaires, observation, and clinical tests for blood glucose and cholinesterase levels. Logistic regression was performed at 95% CI and α = 0.05. Result and Discussion: The results showed that 69.1% of female farmers exposed to pesticides had diabetes with lower cholinesterase levels as a significant indicator (p<0.001; OR=3.897; 95% CI=2.087-7.277). Factors such as working duration ≥10 years (p=0.010; OR=3.564; 95% CI=1.359-9.346), number of pesticides types (p=0.023; OR=3.370; 95% CI=1.187-9.570), spraying duration (p=0.020; OR=3.083; 95% CI=1.197-7.940), and PPE usage (p=0.007; OR=3.601; 95% CI=1.416-9.159) were associated with type 2 diabetes mellitus. Conclusion: Pesticides, particularly organophosphates and carbamates, act as endocrine-disrupting chemicals that impair pancreatic function and increase oxidative stress, contributing to insulin resistance. Female farmers more vulnerable to these effects due to hormonal sensitivity, making gender specific approaches essential. Strict regulations and farmer education are crucial to reduce long-term health risks.